Alternative Indicator of Monetary Policy Stance for Macedonia - Magdalena Petrovska; Ljupka Georgievska (National Bank of the Republic of Macedonia, 2015)
This paper applies a SVAR model which combines different monetary policy instruments to construct an alternative indicator of monetary policy stance in Macedonia. It employs the approach introduced by Bernanke and Mihov (1998) of isolating monetary policy shocks from the whole set of monetary policy instruments that otherwise react to real developments. The residuals from such VAR are cleaned from the central bank's reaction function and represent true monetary policy innovations. Furthermore, we solve the interdependence among different monetary policy instruments contained in the residuals by developing a structural model. We use the model to extract unanticipated policy stance, as an alternative view on the monetary policy.
Keywords: E50; E52; 330; SVAR; Monetary policy stance; Monetary framework